[001] zone-axis bright-field diffraction contrast from coherent Ge(Si) islands on Si(001). - Liao, X; Zou, J; Cockayne, D; Matsumura, S (2004)
Coherent Ge(Si)/Si(001) quantum dot islands grown by solid source molecular beam epitaxy at a growth temperature of 700 degrees C were investigated using transmission electron microscopy working at 300kV. The [001] zone-axis bright-field diffraction contrast images of the islands show strong periodicity with the change of the TEM sample substrate thickness and the period is equal to the effective extinction distance of the transmitted beam. Simulated images based on finite element models of the displacement field and using multi-beam dynamical diffraction theory show a high degree of agreement. Studies for a range of electron energies show the power of the technique for investigating composition segregation in quantum dot islands.